Istradefylline for the treatment of Parkinson's disease: is it a promising strategy?. (2nd November 2018) - Torti, Margherita; Vacca, Laura; Stocchi, Fabrizio
ABSTRACT: Introduction : Istradefylline (ISD) is a new drug developed for the treatment of Parkinson's disease (PD). It is an adenosine receptor A2A antagonists that will represent an important option for patients with advanced PD where it has been demonstrated efficacy in decreasing daily OFF time and is well tolerated. ISD has been marketed in Japan since May 2013. Areas covered : The objective of this review is to summarize evidences emerged from clinical studies that have demonstrated the efficacy of ISD in advanced parkinsonian patients. It will then focus on the potential role in treating non-motor symptoms (NMS) and cognitive decline, which heavily affect quality of life for PD patients. Its putative role as neuroprotective agent will also be discussed. Expert opinion : ISD might represent an alternative option for patients with advanced PD. The reduction of OFF time highlighted in pivotal trials is comparable to that obtained with different levodopa adjunct therapies. The low profile of side effects makes ISD a more suitable drug for advanced patients whose illness is complicated by depression or cognitive impairment. Future studies are warranted to investigate the possible effects of this drug to delay the occurrence of dyskinesia and to impact significantly on NMS.